2005
DOI: 10.1007/s11270-005-0278-x
|View full text |Cite
|
Sign up to set email alerts
|

Liquid and Chemical Fluxes in Precipitation, Throughfall and Stemflow: Observations from a Deciduous Forest and a Red Pine Plantation in the Midwestern U.S.A.

Abstract: Wet deposition (WD), throughfall (TF) and stemflow (SF) measurements undertaken in a deciduous forest show 85% of the WD liquid flux is observed as TF and approximately 2% as SF. TF and SF were observed to be enriched in base cations and accordingly had an average pH of 6.1 and 5.9, respectively relative to a WD pH of 5.1. The seasonal variability of TF pH below the deciduous canopies was more pronounced than that of WD though both exhibited a growing season maximum, and there is evidence that the seasonal var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…Our blank testes showed that for chloride, our tracer, Q R and Q L are both negligible (see also e.g., Cappelatto and Peters 1995;Burkhardt et al 2001b;Rea et al 2001;Pryor and Barthelmie 2005). The upper limit of m po is known in our case (prior-exposure wash-offs being close to or below detection limit).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Our blank testes showed that for chloride, our tracer, Q R and Q L are both negligible (see also e.g., Cappelatto and Peters 1995;Burkhardt et al 2001b;Rea et al 2001;Pryor and Barthelmie 2005). The upper limit of m po is known in our case (prior-exposure wash-offs being close to or below detection limit).…”
Section: Discussionmentioning
confidence: 47%
“…Blank backup filter analysis showed a slight background content for Cl -, 123 lg/filter. Determination of mass collected by the leaves needs special attention in view of potential problems involved in partly related throughfall-measuring techniques (cf., e.g., Lindberg et al 1986;Lovett and Reiners 1986;Pryor and Barthelmie 2005;Watanabe et al 2008). However, our controlled wash-off technique minimizes such problems.…”
Section: Methodsmentioning
confidence: 99%
“…A good measure of the human impact on ecosystems is the deposition of substances reaching them via precipitation (Forsius, Kleemola, & Starr, 2005;Himagenova, 2004;Lundin et al, 2001;Pilkington et al, 2005;Pryor & Barthelmie, 2005;Staelens, De Schrijver, Van Avermaet, Genouw, & Verhoest, 2005). The chemical character of precipitation could be defined using its acidifying potential (Vuorenmaa, 2004).…”
mentioning
confidence: 99%
“…All of the 220 NADP/NTN sites employ an AeroChem-Metrics wet-dry deposition sampler and Belfort 5-780 Universal recording precipitation gauge. Although concerns have been raised about exclusion of light precipitation events by the wet-dry collector due to delay in sampler opening (Claassen and Halm, 1995a,b;Pryor and Barthelmie, 2005), the data are spatially consistent and overall network precision determined from collocated samplers is typically better than ±5% for acid anions, ±10% for base cations and ±20% for NH + 4 (Nilles et al, 1994). Data for this paper were derived from weekly measurements between January 1985 and December 2002 taken from the following NADP sites; IN20, IN22, IN41, KY03, OH09, and IL11 ( Figure 2) which are all located at elevations of between 130-290 m a.s.l.…”
Section: Nadp/ntnmentioning
confidence: 99%